Subcellular redistribution of NHERF1 in response to dehydroepiandrosterone (DHEA) administration in endometrial glands of Wistar rats - Kreimann, Erica Lorena (2013)
To understand the regulation of Na(+)/H(+) exchanger regulatory factor (NHERF1) in polycystic ovarian syndrome, we studied the expression of NHERF1 in uterus of Wistar rats injected with (6 mg/kg) of dehydroepiandrosterone (DHEA) for 7 and 20 days. Immunohistochemistry analysis of NHERF1 showed a substantial shift in the intracellular localization of NHERF1 in endometrial glands and areas of luminal epithelium as early as 7 days of DHEA administration. The NHERF1 accumulated in the "Golgi apparatus area" virtually in all the glands in the 7-day protocol, and in the majority of the glands of 20-day protocol. In contrast, NHERF1 is expressed in the apical membrane and slightly in the cytoplasm of the control epithelium. The subcellular redistribution of NHERF1 could affect the sorting of proteins to the apical membrane and the organization of the apical compartment. © 2013 The Author(s).